Reproductive Performances of PE Doe in Simalungun District - Muhammad Syawal; Solehudin Solehudin (The International Journal of Tropical Veterinary and Biomedical Research, 2019)
The success breeding business of PE goat is closely related to reproductive performance and mortality rates between maternal and calve so that a case study is needed on the reproductive performance of PE Doe. The study was conducted in Taruna Sejahtera Group in Simalungun District, North Sumatera. Twenty nine of PE Does was used. Method was case study. Data was taken from recording list and interview then anlyzed descriptively. The results showed that reproduction characteristics of PE Doe: puberty age 10 month, first mating age 14 month, litter sizes 2 heads, weaning age 2 month, days open 90 days (3 month), post partum mating 4-7 month, calving interval 10 month, milk production averaged 1,2 liter/head/day and parity 4-5 times/head.